Homelessness: Critical reflections and observations from an occupational perspective. Issue 2 (3rd April 2019) - Boland, Leonie; Cunningham, Miranda
ABSTRACT: This comment is the result of our critical reflections, observations and discussions in relation to occupation and homelessness, inspired by our participation in the fourth conference of Occupational Science Europe and informed by our research and experiences in the field. Whilst we acknowledge the growing contribution of occupational science and therapy to homelessness, our practices have led us to identify a number of complex factors that impact this work. In this paper, we discuss issues that influence the participation of homeless persons in everyday life and make suggestions to support occupational participation. At the macro level, we recognise the importance of definitions and categories of homelessness, how legislation can frame the responsibility of homelessness on individuals, and poverty as a causal factor. At the meso level, we explore how charity and power differentials within homelessness services influence participation and propose an occupationally informed approach to homelessness services to enhance meaningful participation. Finally, at the micro level, we focus on interactions with individuals, examining the notion of occupational choice for homeless persons and critiquing traditional rehabilitative approaches. This comment reflects our own critical awakening as occupational therapists situated within a neoliberal society and the value of collaboration between occupational science and occupational therapy. It reinforces the essential role that critical occupational science plays in knowledge generation by attending to the complex structural, cultural and social factors that influence the choices and occupations of homeless persons, which in turn enhances occupation-focused practice.